Observations of acoustic emission in a hydrodynamic bearing - Mirhadizadeh, S. A.; Mba, David (Emerald Group Publishing Limited, 2009)
Purpose - Numerous studies have been conducted in the field of acoustic emission (AE) technology applied to rotating machine fault diagnosis. Principally, most of the work to date has been focused on correlating AE activity to the defect condition on rolling element bearings with limited investigations on hydrodynamic bearings. This paper aims to address this issue. Design/methodology/approach - This paper presents experimental tests aimed at understanding the influence of speed and load on generation of AE in a hydrodynamic bearing. Findings - The research presented shows that the power losses associated which hydrodynamic bearing has a direct influence on the generation of AE. Research limitations/implications - Further research should include the application of the proposed methodology on a broad range of operational machines employing hydrodynamic bearings. Practical implications - In developing the AE technology for monitoring hydrodynamic bearings operated under variable speed and load conditions, it is essential that a relationship between the operational variables and the generation of AE is established, and this paper explores such a relationship. Originality/value - The paper presents the first known correlation between AEs and the operating parameters of a hydrodynamic bearing.
Keywords: Bearings; Condition monitoring; Hydrodynamics